Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen